The Nurse Mentor's Companion - Craig, Kim; Craig, Kim; Smith, Barbara (SAGE Publications, 2014)
This is a new highly practical guide to doing mentoring in practice. It explains how to support student nurses from the day that they arrive on placement in six straightforward, concise and clear chapters. The book is packed full of resources and learning features, including: Action plans for managing your student Checklists of resources you will need Tips for best practice Case studies covering all fields of nursing Reflective questions which challenge you to question your assumptions. Chapters are tied closely to the NMC standards, and cover essential topics including assessment, the role of the sign-off mentor and team-working. The Nurse Mentor$1 (Bs Companion is valuable reading for all nurses taking mentoring courses across the UK, and as they go on to mentor in practice.s